TOWARD MULTICULTURALISM IN DEALING WITH MINORITY GROUP Study Case: Saminism (A Social Work Perspective) - Nina Mariani Noor (Politika: Jurnal Ilmu Politik, 2018)
Multiculturalism is a term that is actually has been considered by Indonesian people long before the establishing of the nation-state. It can be seen from the underlying concept of multiculturalism in Indonesia that is comprised in the national philosophy Pancasila and the UUD 1945 Constitution. However, the implementation of multiculturalism in Indonesia did not start at that time.The implementation of multiculturalism in Indonesia emerged when the discourse of multiculturalism have spread over the world. Consequently, Indonesia, as a country which has multi-ethnic and multicultural society have to practice it both socially and politically.Since multiculturalism regards all groups involving in the State, both dominant groups and non-dominant ones, minority groups are had to have same opportunities in social, economy and political aspects. However, implementing multiculturalism is not as simple as imagined. There are several obstacles faced. On one hand, multiculturalism seems to be the best means in reaching social justice and equality among people. On the other hand, the social system constructed which is in domination of one or small cultural groups are difficult to be changed.Regrettably, the State as the holder of the authority is in dominant groups’ hand and it is trapped in defending status quo. As a result, the policies conducted relating to multiculturalism only benefit dominant group, whereas minority groups get nothing. It will be better if minority groups directly involved in deciding program that will be conducted in their community so that both the State and the minority group will benefit from the program.